2022
DOI: 10.36660/abc.20220058
|View full text |Cite
|
Sign up to set email alerts
|

Disparidade de Gênero na Autoria Principal e Sênior em Periódicos Brasileiros de Cardiologia

Abstract: Fundamento: Apesar da importância das mulheres na pesquisa clínica, não existe uma avaliação da fração de mulheres em posições de autoria nos periódicos de cardiologia da SBC. Objetivos: Avaliar a fração de mulheres autoras na International Journal of Cardiovascular Sciences (IJCS) e nos Arquivos Brasileiros de Cardiologia (ABC Cardiol) nas últimas décadas. Métodos: Realizamos busca dos artigos originais dos ABC Cardiol, entre 2000 e 2019, e da IJCS, entre 2010 e 2019. Foi feito levantamento do número de prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The majority of articles with female first authors are concentrated in the country’s major urban centers, highlighting regional disparities in research opportunities and the need for investment and support in rural areas. This pattern is consistent with previous Latin American studies (5) (6), highlighting the continued underrepresentation of females as first and last authors in research articles. It has even been demonstrated that women’s representation is declining in Latin America, primarily in the medical sciences (11).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The majority of articles with female first authors are concentrated in the country’s major urban centers, highlighting regional disparities in research opportunities and the need for investment and support in rural areas. This pattern is consistent with previous Latin American studies (5) (6), highlighting the continued underrepresentation of females as first and last authors in research articles. It has even been demonstrated that women’s representation is declining in Latin America, primarily in the medical sciences (11).…”
Section: Discussionsupporting
confidence: 91%
“…In Latin American countries, similar gender disparities in authorship and academia persist in the medical field. Tinoco et al (5) discovered that female authors were less likely to hold first and last positions in Brazilian Cardiology journals. A subsequent investigation by Campos et al (6) revealed that women were frequently underrepresented on editorial boards in Latin American surgical journals.…”
Section: Introductionmentioning
confidence: 99%
“…In authorships of scientific publications, the inequality remains present. For instance, in a Brazilian Surgical Journal, 72.2% of the authors were men and according to a study, in two cardiology journals, around 70% of the last authors were male ( Mesquita et al, 2022 ).…”
Section: Gender Disparity In Stemmentioning
confidence: 97%